Distribución espacial de la población y desarrollo: notas acerca de los asentamientos urbanos de América Latina - Jordán, Ricardo (Revista EURE - Revista de Estudios Urbano Regionales, 1982)
The author formulates that "the urbanization process is one of the most prominent components of the spatial distribution of the population and, thus, one of the most significant dimensions of the topics relating human settlements. At the same time, the different changes represented by the urbanization process constitute a technical and scientific challenge that appears quite close to the analysis of the multiple dimensions of social change and development". This is followed by a schematic presentation of socioeconomic and demospatial expressions of urbanization in Latin America, aimed at the detection of relevant issues to be examined in deep. At the same time, the author poses some ideas about the basic conditions that should be reached by research oriented to the formulation of strategies and policies for the spatial redistribution of the population. He finds that the urbanization process poses an enormous challenge to latinamerican countries. The apparent "inevitable" effects derived from concentration of population in a few cities -urban decay, lack of or severe shortages of services, congestion, and all sorts of pollution- deserve a great planning effort and not a mere use of usually expensive and inefficient palliatives. This historic challenge demands the analysis of the relations between urbanization and economic and social development, taking into account the effects generated and the definition of criteria for the formulation of strategies as well as the selection of tools for action. Scientists in Latinoamerica have thus a double task: the explanation of social and economic processes and the definition of criteria for modifying them.